'Because I love him': Children's relationships to their parents in the context of intimate partner violence. (May 2021) - Henze-Pedersen, Sofie
This paper investigates how children experience and practice parental relationships after moving to a women's refuge. Most research has explored the moving and separation process from women's perspectives, but this paper focus on children's perspectives. Based on ethnographic fieldwork and interviews with children at a refuge, the analysis shows how children's parental relationships – despite the violence – remain important under difficult family circumstances, and how children practice intimate social bonds while being embedded within complex family relationships. This brings attention to the wider contexts of children's relationships and how these affect children's experiences and practices of intimate social bonds.